Análise das tecnologias digitais de informação e comunicação como mediadoras de relações e da construção do conhecimento de adolescentes - Giacometti-Rocha, Erika (2015)
In Brazil, the National Broadband Plan (PNBL) was one of the policies implemented since 2010 to increase the share of the population with access and possibility of using digital media, especially in the Latin American scenario. Not least, the need to assess the impact of the massive insertion of digital media was notorious, analyzing sociocultural and cognitive aspects. It starts from the premise of the interaction between subjects and technologies as a process that does not distance subject and its technique, being the technique part of the human being in society and being both agents in this interaction. This research examines the sociocultural and cognitive impacts among adolescents with the mediation of the intensive use of digital media and chose the construction of knowledge for school education as a research field. Thus, the general objective is to analyze the impact of digital media as mediators of social relations and the construction of the knowledge of adolescents. We therefore assume the following specific objectives: a) to understand the presence and use of digital media in the school context, addressing the main characteristics and difficulties; b) investigate the social impact of spatial mobility and social interactions according to type of digital media; c) analyze the cognitive impact by observing study strategies according to the adolescents' daily access time, and d) examine the cultural impact of digital media use through the preferences of content accessed on the Internet and by forming groups in it. The research is descriptive in nature and the methodology is qualitative-quantitative. The instruments used were questionnaire and interviews. The criterion adopted to determine "intensive use of the Internet" was established in 3 hours, according to data collected on national average daily internet connection time, together with data from the questionnaire applied in the research. The results suggest that the data did not show a significant correlation between their type (smartphones, tablets, computers, etc.) and socio-cultural and cognitive effects, mainly due to adolescents' content, which does not differ from other contexts like the virtual and by its chosen strategies of study, that do not demonstrate accelerated development of its autonomy in the construction of the knowledge. However, we can affirm that there is a significant correlation in the comparison between Intensive and non-Intensive use in age, gender, type of school, whether there is or not computer, Internet or not, own other Internet devices or not, own video game or not, in the access content of interest Personal access to study, in the participate in groups on the Internet, in the access smartphones and iPhones at class to talk and send videos. In all other variables, there was no such correlation. Statistically, the difference may not be sufficient to assert impacts on all analyzed variables. At the same time, coincidentally, always, the group that uses the Internet intensively presents the highest percentages, even with minimal difference. This may not amount to much, but when we talk about change, especially when there are n resistance factors, this minimal persistent difference presented higher for the group that uses the Internet for more time daily may be an incentive to re-analyze them.